Valuing Environmental Amenities Using Stated Choice Studies A Common Sense Approach to Theory and Practice - Kanninen, Barbara J.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2007)
This book provides practical, research-based advice on how to conduct high-quality stated choice studies. It covers every aspect of the topic, from planning and writing the survey, to analyzing results, to evaluating quality. Chapters by highly-regarded academics and professionals are provided on rarely-discussed topics such as "supporting questions” and experimental design, as well as state-of-the-art multinomial choice modelling, attribute processing, the role of information, and lessons learned from the field of experimental economics. There is no other book on the market today that so thoroughly addresses the methodology of stated choice. Academics and practitioners in fields such as environmental, health and transportation economics, and marketing, will need this book on their shelves – and they will refer to it often.
Contributing Authors -- Preface -- Acknowledgments -- 1. Getting Started, Carol Mansfield and Subhrendu Pattanayak -- 2. Survey Methodologies for Stated-Choice Studies, Patricia A. Champ and Michael P. Welsh -- 3. Supporting Questions in Stated-Choice Studies, Alan Krupnick and W. Vic Adamowicz -- 4. Making Choice Studies Incentive Compatible, Glenn Harrison -- 5. How and How Much? The Role of Information in Stated-Choice Questionnaires, Kristy E. Mathews, Miranda L. Freeman and William H. Desvousges -- 6. Attribute Processing in Choice Experiments and Implications on Willingness to Pay, David A. Hensher -- 7. Experimental Design for Stated-Choice Studies, F. Reed Johnson, Barbara Kanninen and Matthew Bingham -- 8. Basic Statistical Models for Stated-Choice Studies, Anna Alberini, Alberto Longo and Marcella Veronesi -- 9. Advanced Choice Models, Joffre Swait -- 10. Computer Software to Estimate Choice Models, Daniel Hellerstein -- 11. Judging Quality, V. Kerry Smith -- Index.
Keywords: Environmental economics; Social sciences; Econometrics; Environmental Economics; Methodology of the Social Sciences; Econometrics